Strategi Komunikasi Krisis Organisasi Dalam Menghadapi Isu Boikot Unilever - Nurul Amalia Fitriani; Arumbinang Pindoyoga Ahsan; Selvi Novitasari; Ananta Priscila; Isna Siskawati (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study examines the crisis communication strategy of PT Unilever Indonesia Tbk in responding to the boycott calls arising from the Palestine-Israel conflict during 2023-2024. The approach used is qualitative with a case study method, collecting data through in-depth interviews. The findings reveal that the company responded quickly with a dedicated team actively monitoring and managing the issue. The communication strategy emphasized transparency, empathy, and adjustment to the cultural sensitivities and social values of the local community. Effective coordination within the organization was also a key factor in delivering consistent and effective messages to the public and business partners. Through these efforts, Unilever succeeded in building a clear and factual narrative that helped to calm public anxiety and panic. The strategy reflects the adaptive application of the Situational Crisis Communication Theory (SCCT), managing the crisis by balancing global business interests with Indonesia's local values. Overall, the communication was not only focused on direct problem-solving but also on building long-term relationships with the public through transparent and culturally sensitive communication. This approach proved effective in maintaining the company’s reputation amid a complex and dynamic crisis.